ANALISIS PERSENTASE PENDUDUK PENDERITA HIPERTENSI YANG MENDAPATKAN PELAYANAN KESEHATAN DI NUSA TENGGARA BARAT TAHUN 2019-2021 - Afid Rakhma Dianita; Ani Puspasari; Charisma Chammy Delanian; Dian Ayu Prihatini; Eva Ratih Maharani; Fingky Amanda Putri; Frida Alfina Darayanti; Hafzah Susanti; Hepi Tahta Alfina (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2024)
Hypertension is a problem throughout the world and is one of the main risk factors for cardiovascular disease. Hypertension or high blood pressure can be caused by several factors, both factors that can be changed and cannot be changed. This study aims to find out the percentage of the population with hypertension who receive health services in each region in West Nusa Tenggara province based on age and gender. This research method uses a descriptive research type with samples, namely data on residents suffering from hypertension in 10 districts in West Nusa Tenggara (NTB) Province in 2019-2021 with a sampling technique, namely a non-probability technique of purposive sampling type. The research results showed that of the 119,500 participants consisting of men and women, the majority of participants were over 18 years old. male participants numbered 135,453 while the number of women was 142,889. The results of the research obtained a distribution of respondents based on gender between men (62,09%) and women (74,79%). Hypertension in teenagers needs to be watched out for. Suggestions, it is necessary to carry out early prevention efforts related to diet and lifestyle in adolescents, including: changing diet, limiting the use of salt to 4-6 grams per day, foods containing baking soda, seasonings and food preservatives, reducing food intake. which contains high cholesterol, stop smoking, drinking alcohol, and exercise regularly.